(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: The occurrence of Down’s syndrome is usually associated with advancing maternal age and increased parity. Objectives: This study explores the risk factor associated with the occurrence of Down’s syndrome for different age groups. Methods: Blood sample from suspected Down’s syndrome babies were prepared for chromosomal preparation. A hundred and fifty four blood samples from patients suspected of being Down’s syndrome baby came with variable features which raise the suspicion of being Down’s. Results: The study groups were 65 male and 89 female. Seventy seven (77) were the first member of the family, 68 were born for young mothers with an age between 15-34 years. Only nine were born for old mothers aged between 35-43 years. Seventy three were members of the family other than the first. Twenty six were born for mothers aged between 35-43 years, while the other 47 were born for mothers aged between 15-34 years. Chromosomal study for 4 cases revealed normal chromosomal findings. Conclusion: This study may show that young Iraqi mothers (under 35 year) carry high risk of having down’s baby both in multi as well as primigravida. Key words: Down’s syndrome, trisomy, primigravida, multigravida, Chromosome.